Evaluation of thermal shock fracture resistance of B4C/CNT composites with a high-frequency induction-heating furnace. (2019) - Maki, R.S.S.; Fajar, M.; Maletaskic, J.; Gubarevich, A.V.; Yoshida, K.; Yano, T.; Suzuki, T.S.; Uchikoshi, T.
Abstract: Boron carbide (B4 C) ceramics with high thermal stability and relatively large cross-section for fast neutron absorption have been used as neutron absorbers of the control rods for the fast breeder reactors (FBR). However, cracks induced in B4 C pellets due to thermal stress and swelling during neutron irradiation have been one of the practical problems, which leads to short lifetime of the control rods. It is essential to improve the mechanical properties of B4 C ceramics for suppressing the cracking of B4 C pellets and to enhance the thermal conductivity for relaxation of thermal stress during neutron irradiation. According to our previous study, the fracture toughness and thermal conductivity of B4 C ceramics were enhanced by carbon nanotube (CNT) addition. In the present work, we report the dependence of the thermal and mechanical properties on the CNT-orientation in the sintered body prepared by hot-pressing and the enhancement of thermal shock fracture resistance of the obtained B4 C/CNT composites. The thermal shock fracture resistance of hot-pressed B4 C/CNT composites was evaluated by means of thermal shock test with a high-frequency induction-heating furnace. The dependence of the thermal properties on the CNT-orientation and the enhancement of thermal shock resistance of B4 C ceramics were confirmed.